A novel direct activator of AMPK inhibits prostate cancer growth by blocking lipogenesis - Giorgia Zadra; Cornelia Photopoulos; Svitlana Tyekucheva; Pedram Heidari; Qing Ping Weng; Giuseppe Fedele; Hong Liu; Natalia Scaglia; Carmen Priolo; Ewa Sicinska; Umar Mahmood; Sabina Signoretti; et al. (EMBO Molecular Medicine)
Abstract 5′AMP‐activated kinase (AMPK) constitutes a hub for cellular metabolic and growth control, thus representing an ideal therapeutic target for prostate cancers (PCas) characterized by increased lipogenesis and activation of mTORC1 pathway. However, whether AMPK activation itself is sufficient to block cancer cell growth remains to be determined. A small molecule screening was performed and identified MT 63–78, a specific and potent direct AMPK activator. Here, we show that direct activation of AMPK inhibits PCa cell growth in androgen sensitive and castration resistant PCa (CRPC) models, induces mitotic arrest, and apoptosis. In vivo, AMPK activation is sufficient to reduce PCa growth, whereas the allelic loss of its catalytic subunits fosters PCa development. Importantly, despite mTORC1 blockade, the suppression of de novo lipogenesis is the underpinning mechanism responsible for AMPK‐mediated PCa growth inhibition, suggesting AMPK as a therapeutic target especially for lipogenesis‐driven PCas. Finally, we demonstrate that MT 63–78 enhances the growth inhibitory effect of AR signaling inhibitors MDV3100 and abiraterone. This study thus provides a rationale for their combined use in CRPC treatment.